Leaf turgor loss point is one of the best predictors of drought-induced tree mortality in tropical forest - Su, Rui; Liu, Hui; Wang, Chen; Zhang, Hui; Cui, Jie (Frontiers in Ecology and Evolution, 2022)
Accurately predicting global drought-induced tree mortality remains a major challenge facing plant science and ecology. Stem hydraulic safety margin (HSM, the difference between water potential at the minimum value and the value that causes xylem vulnerability to embolism) performs as one of the best hydraulic traits in predicting global drought-induced tree mortality, however HSM is time-consuming and very difficult to measure. We proposed to use leaf turgor loss point (TLP, the water potential at which leaves start to wilt) as a proxy for HSM because HSM may be highly correlated to TLP, as both of them are tightly linked with water potential changes after stomatal closure. Since TLP is more easy and rapid to measure than HSM, if we find strong HSM-TLP relationships at the global scale, TLP can be used in predicting global drought-induced tree mortality. However, no study has quantified the relationships between HSM and TLP at the global scale. Here we draw together published data on HSM and TLP for 1773 species from 370 sites worldwide to check whether HSM and TLP are highly associated. We found that HSMs and TLPs are merely highly related in tropical forests, thus TLP can be a reliable surrogate of HSM to predict drought-induced tree mortality in tropical forest. Here we are certainly not advocating for the use of TLP instead of HSM to predict drought-induced tree mortality in tropical forests, but simply for predicting drought-induced tree mortality in tropical forests in supplementary of HSM in the future.